2018
DOI: 10.1007/s10393-018-1369-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the Mass Distribution of LPG Stoves in Rural Communities of Ghana

Abstract: Household air pollution (HAP) is a leading cause of morbidity and mortality worldwide. To limit HAP exposure and environmental degradation from biomass fuel use, the Government of Ghana promotes liquefied petroleum gas (LPG) use in rural Ghana via the Rural LPG program (RLP). We assessed the experiences of the RLP in 2015, 2 years after its launch. A mixed methods approach was used involving Focus Group Discussions (19) and in-depth interviews (25). In addition, a survey questionnaire was administered to elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Most families reported continuing cooking with traditional clay stoves in order to save fuel, and this has been previously reported in rural India [20] and rural Ghana [21]. In a trial environment, we need to ensure that households adhere to the trial protocol and switch cooking fuels to LPG, so that the LPG intervention will be efficacious.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most families reported continuing cooking with traditional clay stoves in order to save fuel, and this has been previously reported in rural India [20] and rural Ghana [21]. In a trial environment, we need to ensure that households adhere to the trial protocol and switch cooking fuels to LPG, so that the LPG intervention will be efficacious.…”
Section: Discussionmentioning
confidence: 95%
“…The behaviour change materials in our large trial also address the safety concerns about LPG cooking, which has been previously identified [17,21]. Safety mostly regarding the LPG cylinders is being included early in the trial so that it does not interfere with recruitment of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Kerosene subsidies were replaced with LPG subsidies (Thoday et al, ). The government of Ghana started to distribute LPG stoves to the rural population in 2013, but barriers to access to fuel (e.g., cost, distance to the distributor) limit adoption and continued use (Abdulai et al, ). In Peru, the Fondo de Inclusión Social Energético (FISE) LPG Promotion Program has achieved a broad distribution of LPG stoves, but households tend to keep biomass stoves for similar access issues (Pollard et al, ).…”
Section: Energy Access: Household Cooking Fuel Transitionmentioning
confidence: 99%
“…Access and quality of access to fuels further determine if households sustain fuel use after initial technology adoption. A study of 200 randomly drawn participants in the free rural LPG stove program in Ghana shows that the use of distributed LPG stoves is impeded by a lack of continuous access to fuel supply encouraging the parallel use of biomass (Abdulai et al, ). Among other factors, the weight of LPG cylinders is a deterrent if transportation is not available; similar results can be found in Peru (Pollard et al, ).…”
Section: Energy Access: Household Cooking Fuel Transitionmentioning
confidence: 99%
“…In Ghana, about 74% of households, especially those in rural settings, use traditional biomass fuels for cooking whilst just about 18% (mostly in cities) use LPG for cooking [ 14 ]. Even when households have clean cookstoves and fuels, stove stacking (i.e., switching between clean cookstoves and other biomass traditional stoves) is still practiced for varied reasons, paramount of which are high costs of using clean cooking fuels and type of food cooked [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%